(untitled) - Trần, Thị Diễm My (Cần Thơ, 2019)
This study aims to investigate the employability attributes employers require for bachelor graduates of an ETI program in the Mekong Delta of Vietnam. In addition, it also explores the suggestions of these employers for the ETI program in the Mekong Delta of Vietnam.
Keywords: Translating and interpreting